The origins of the canon of the Hebrew Bible an analysis of Josephus and 4 Ezra - Ossándon, Juan Carlos 1976- (Leiden Boston Brill, 2019)
"In The Origins of the Canon of the Hebrew Bible: An Analysis of Josephus and 4 Ezra, Juan Carlos Ossandón Widow examines the thorny question of when, how, and why the collection of twenty-four books that today is known as the Hebrew Bible was formed. He carefully studies the two earliest testimonies in this regard--Josephus' Against Apion and 4 Ezra--and proposes that, along with the tendency to idealize the past, which leads to consider that divine revelation to Israel has ceased, an important reason to specify a collection of Scriptures at the end of the first century CE consisted in the need to defend the received tradition to counter those that accepted more books"--
Includes bibliographical references
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Josephus, Flavius; Josephus, Flavius; Bible -- Canon -- History; Bible -- Criticism, interpretation, etc; Bible -- Canon -- History; Bible -- Criticism, interpretation, etc -- Bible -- Bible -- Contra Apionem (Josephus, Flavius); Judaism -- Apologetic works -- History and criticism; Judaism -- Apologetic works -- History and criticism; Judaism -- Apologetic works; Bible; Contra Apionem (Josephus, Flavius); Judaism; Josephus, Flavius; Criticism, interpretation, etc; History